Pengaruh non-debt tax shield, tangibilitas, human capital, risiko bisnis, ukuran perusahaan, pertumbuhan, likuditas dan profitabilitas terhadap financial leverage pada sektor komunikasi - ANDREAS HIMAWAN; SATRIYO WIBOWO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
This study investigates the determinants of capital structure theoretically and empirically in Indonesia. Since several decades, capital sructure has remained puzzle. This study will further provide a logical explanation towards the factor affecting capital structure by adding unique variable that is human capital as the determinant on financial leverage. Panel data is used for analysis and ordinary least square method (OLS) for regression analysis which minimizes error in estimation results. The data was taken from annual financial statement of the telecommunication firm listed in IDX (Indonesia Stock Exchange), using a sample of 7 telecommunication listed firms for 2010-2014. The dependent variable was Financial Leverage (Total Liabilities to Total Assets) while the independent variable were Non-Debt tax shield, Tangibility, Human Capital, Firm Size, Business Risk, Growth, Liquidity and Profitability. The research findings shows that the variables of Non-Debt tax shield, Tangibility, Human Capital, Business Risk, and Profitability are positively related with Financial Leverage, while Firm Size, Growth and Liquidity are negatively related with Financial Leverage. Business Risk is statistically significant determinants of Capital Structure. While Non-Debt tax shield, Tangibility, Human Capital, Firm Size, Growth, Liquidity and Profitability are statistically insignificant determinants of Capital Structure.